2017
DOI: 10.1002/btpr.2574
|View full text |Cite
|
Sign up to set email alerts
|

High yield purification and first structural characterization of the full‐length bacterial toxin CNF1

Abstract: The Cytotoxic Necrotizing Factor 1 (CNF1) is a bacterial toxin secreted by certain Escherichia coli strains causing severe pathologies, making it a protein of pivotal interest in toxicology. In parallel, the CNF1 capability to influence important neuronal processes, like neuronal arborization, astrocytic support, and efficient ATP production, has been efficiently used in the treatment of neurological diseases, making it a promising candidate for therapy. Nonetheless, there are still some unsolved issues about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This new version of the protein was named An2-CNF1-H8, as it still possessed a C-terminal polyhistidine tag (Figure 1A). The recombinant expressions of both CNF1-H8 and An2-CNF1-H8 were carried out at a low temperature of 15 • C, as previously reported [13]. The analysis of total cellular extracts obtained at the end of the bacterial growths indicated that an overexpression was clearly visible for both the constructs via SDS-polyacrylamide gel electrophoresis (PAGE) (Figure 1(B1)) and western blot (Figure 1(B2)).…”
Section: Design and Production Of A Cnf1 Variant Bearing The Potentiality To Cross The Bbb When Peripherally Injectedmentioning
confidence: 83%
See 4 more Smart Citations
“…This new version of the protein was named An2-CNF1-H8, as it still possessed a C-terminal polyhistidine tag (Figure 1A). The recombinant expressions of both CNF1-H8 and An2-CNF1-H8 were carried out at a low temperature of 15 • C, as previously reported [13]. The analysis of total cellular extracts obtained at the end of the bacterial growths indicated that an overexpression was clearly visible for both the constructs via SDS-polyacrylamide gel electrophoresis (PAGE) (Figure 1(B1)) and western blot (Figure 1(B2)).…”
Section: Design and Production Of A Cnf1 Variant Bearing The Potentiality To Cross The Bbb When Peripherally Injectedmentioning
confidence: 83%
“…We previously reported an efficient strategy for the production and purification of the CNF1 toxin as a his-tagged recombinant protein (CNF1-H8) from E. coli extracts [13]. In the present manuscript, we describe the production and purification of the An2-CNF1-H8 variant, a CNF1 variant displaying an N-terminal Angiopep tag potentially endowed with the ability to allow BBB crossing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations